First metagenome report of Haemaphysalis bispinosa ticks of Moa buffalo from Southwest Maluku District, Indonesia - PRASETYARTI UTAMI; RONY MARSYAL KUNDA; YOFIAN ANAKTOTOTY (Nusantara Bioscience, 2024)
Abstract. Utami P, Kunda RM, Anaktototy Y. 2024. First metagenome report of Haemaphysalis bispinosa ticks of Moa buffalo from Southwest Maluku District, Indonesia. Nusantara Bioscience 16: 130-138. Ticks are vectors of pathogenic organisms such as bacteria, protozoa, and viruses, which are potentially fatal to humans and livestock. The Haemaphysalis bispinosa Neumann, 1897 is a tick species with three mammalian hosts in Asia and Australia, including Indonesia, with the highest infestation in cattle (Bos taurus Linnaeus, 1758) and sheep (Ovis aries Linnaeus, 1758). The H. bispinosa is known to transmit many pathogens, but studies on the profile and structure of the microbiota are still very limited. This study aims to investigate the abundance and diversity of microbiota in H. bispinosa to evaluate the bacterial community's structure and to identify and examine potential zoonotic agents from buffalo. Amplification in this study used primers from the region (V1-V9) of the 16S rRNA gene. Metagenomic analysis shows that the microbiota community structure is dominated by non-zoonotic bacteria (96.83%), and zoonotic bacteria are found in the percentage (3.17%). Zoonotic agents were dominated by members of the genus Rickettsia (71.82%), Ehrlichia (19.19%), Romboutsia (3.16%), Anaplasma (2.43%), Coxiella (2.24%), Staphylococcus (0, 48%) and Streptococcus (0.43%). Overall, 16 species were found in H. bispinosa, i.e., 11 species belonging to the genus Rickettsia, 2 species from the genus Ehrlichia (i.e., Ehrlichia canis and Ehrlichia minasensis), and 1 species each belonging to the genera Anaplasma, Coxiella, and Romboutsia. It was concluded that the abundance of the microbial community in H. bispinosa based on metagenome analysis using the 16S rRNA gene from Moa buffalo in the Southwest Maluku District was classified as having a diverse abundance of species.